Kentucky's Rebel Press : Pro-Confederate Media and the Secession Crisis - Craig, Berry (Book collections on Project MUSE., 2018)
Throughout the Civil War, the influence of the popular press and its skilful use of propaganda was extremely significant in Kentucky. In this compelling and timely study, Berry Craig analyses the media's role in both reflecting and shaping public opinion during a critical time in US history.